1990
DOI: 10.1007/bf00419936
|View full text |Cite
|
Sign up to set email alerts
|

Aged-onset Kienb�ck's disease

Abstract: Kienböck's disease with onset after 50 years of age was studied. Of 127 patients with Kineböck's disease seen over the past 30 years, the cases of 15 (12 female, 3 male) were analyzed. The average age of onset was 58.3 years. Five specimens were obtained operatively in which necrosis of the lunate bone mixed with empty lacunae was identified, as was bony remodelling. Ulnar variance in the aged diseased group (group A) was smaller than that of the aged control group (group C). Moreover, it was noteworthy that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…These characteristics were found in our patient. In addition, based on the clinical study, Yoshida et al 8 indicated that osteoporosis is an aetiologic factor of Kienböck's disease. Senile or post-menopausal osteoporosis in our patient might be a risk factor for avascular necrosis of the lunate after repetitive minor trauma through the practice of kendo.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics were found in our patient. In addition, based on the clinical study, Yoshida et al 8 indicated that osteoporosis is an aetiologic factor of Kienböck's disease. Senile or post-menopausal osteoporosis in our patient might be a risk factor for avascular necrosis of the lunate after repetitive minor trauma through the practice of kendo.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the elderly patient, Kienböck disease behaves differently in comparison to the pediatric and adult cohorts. [10][11][12][13][14] In Kienböck patients older than 70 years, there is less negative ulnar variance, a higher prevalence in women, who had more advanced radiological changes. 11 At a mean follow-up of 5.6 years, all 15 patients progressed to stage IV disease but had good-to-excellent clinical outcomes without surgery.…”
mentioning
confidence: 99%
“…Three of the 4 reported cases in patients over the age of 65 are women, with the oldest being 75 years old. [5][6][7][8] Therefore osteoporosis, seen commonly in elderly women, may be a contributing factor to the development of Kienböck's disease whereas repetitive microtrauma may account for the majority of cases in the younger male population. …”
Section: Discussionmentioning
confidence: 97%
“…Three of the 4 reported cases of Kienböck's disease in patients age 65 and older are women, with the oldest being 75 years of age. [5][6][7][8] The following case shows an additional presentation of Kienböck's disease in a woman over 65 years old who had successful PRC for this condition.…”
mentioning
confidence: 93%